A Comparative Study between the Use of Role Play and Discussion Method in Teaching Speaking Ability - Syafrizal Syafrizal; John Pahamzah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
The study aims to investigate if role play and discussion methods can improve students’ speaking skills significantly. The researcher also attempts to investigate whether role play or discussion method that better enhancing the students’ speaking performance after the teaching-learning process conducted. To achieve these aims, the quasi-experimental research design is employed. The data were gathered from 60 students of twelfth grade in one of the vocational high schools in Pandeglang, Banten. Students from two classes were taken randomly and divided into experimental and control groups. Some instruments like pre-test - post-test were employed to collect the data. At the end of the study, many advantages were found to improve the students’ speaking skill including vocabulary, grammar, and pronunciation aspect. Both groups indicated to experience improvement, but the experimental group showed more advanced enhancement indicated by their achieving to reach the ‘good’ category in speaking. While none of the students from the control group could get that. Conclusively, students taught by the discussion method show more improvement with 19.93 as their mean score. While students by role-play method have 13.73 as their mean score. It is significantly different from both methods indicated by the significance value score of 0.14 which is less than 0.05. Hence, the discussion method is more effective than the role-play method in improving students’ speaking ability. For that reason, it is recommended for teachers to use discussion method to improve students’ speaking comprehension.